Plant factories versus greenhouses: Comparison of resource use efficiency. (February 2018) - Graamans, Luuk; Baeza, Esteban; van den Dobbelsteen, Andy; Tsafaras, Ilias; Stanghellini, Cecilia
Abstract: Research on closed plant production systems, such as artificially illuminated and highly insulated plant factories, has offered perspectives for urban food production but more insight is needed into their resource use efficiency. This paper assesses the potential of this 'novel' system for production in harsh climates with either low or high temperatures and solar radiation levels. The performance of plant factories is compared with cultivation in traditional greenhouses by analysing the use of resources in the production of lettuce. We applied advanced climate models for greenhouses and buildings, coupled with a lettuce model that relates growth to microclimate. This analysis was performed for three different climate zones and latitudes (24–68°N). In terms of energy efficiency, plant factories (1411 MJ kg −1 dry weight) outperform even the most efficient greenhouse (Sweden with artificial illumination; 1699 MJ kg −1 dry weight). Additionally, plant factories achieve higher productivity for all other resources (water, CO2 and land area). With respect to purchased energy, however, greenhouses excel as they use freely available solar energy for photosynthesis. The production of 1 kg dry weight of lettuce requires an input of 247 kWhe in a plant factory, compared to 70, 111, 182 and 211 kWhe in greenhouses in respectively the Netherlands, United Arab Emirates and Sweden (with and without additional artificial illumination). The local scarcity of resources determines the suitability of production systems. Our quantitative analysis provides insight into the effect of external climate on resource productivity in plant factories and greenhouses. By elucidating the impact of the absence of solar energy, this provides a starting point for determining the economic viability of plant factories. Highlights: Energy, water, CO2, and land are the parameters used to compare plant factories to greenhouses for resource use efficiency. Plant factories use all four resources more efficiently than greenhouses in the three case studies evaluated. Lettuce production in the plant factories requires 14%, 33%, 142% and 251% more purchased energy than in the greenhouses. The production of lettuce in the plant factories instead of the greenhouses could reduce water use by 28%, 92%, 93% and 95%. The advancement in LED efficiency is paramount, but presumably not sufficient to ensure the feasibility of plant factories.